Підвищення ефективності вантажних автоперевезень шляхом використання триланкових автопоїздів - Бадейнов, Олександр (ТзОВ «Галицька видавнича спілка», 2021)
The paper states the necessity of the improvement of the elastic-damping characteristics and the design of hitch devices to reduce dynamic shock loads and a hitch wear during three-unit tractor-trailer movement due to the adjustment of traction-hitch devices damping characteristics.
Improving the efficiency of freight transportation with the use of three-unit tractor-trailers
Keywords: 656.13